Living Kidney Donors' Information Needs and Preferences. (March 2016) - Traino, Heather M.; Nonterah, Camilla W.; Gupta, Gaurav; Mincemoyer, Jodi
Introduction: Past research suggests the information exchanged from transplant centers to potential living kidney donors is, in many cases, suboptimal. The purpose of this study was to assess donors' perceptions of the information provided while considering living donation. Methods: Semistructured telephone interviews conducted with 81 past living donors seen at 1 mid-Atlantic transplant center assessed the extent to which living kidney donors deemed Centers for Medicare and Medicaid Services (CMS)-mandated information useful to making a decision about donation and to which more information was or would have been desired before donating. Understanding of and satisfaction with the information was also assessed. Results: Participants were primarily white (67.9%), females (67.9%), with an average age of 57.8 years. Perceived usefulness ranged from a mean of 3.1 for the confidentiality of the transplant center's communication to 4.1 for postoperative care and short-term medical risks of donation. Donors of minority descent as well as those with more education and less income found the information provided most useful. Few donors desired additional information about the right to opt out of (8.6%) or decline (13.6%) donation; however, most wanted more information regarding the risk of being refused health, disability and/or life insurance after donating (77.8%), and insurance coverage for future health problems (66.7%). Discussion: This study revealed limited usefulness of certain CMS-mandated topics and a desire for additional information about donation. Efforts to standardize the informed consent process should incorporate donors' perspectives as to the specific topics, quantity of information, and the mode of communication found most useful when considering living donation.